Mediasi kepuasan kerja pada peran kesesuaian individu-pekerjaan terhadap komitmen organisasi karyawan generasi Z perusahaan rintisan - Shafira, Cita Nadiana; Zulaifah, Emi (Jurnal Psikologi Ulayat, 2025)
Startup companies in Indonesia attract generation Z employees due to their flexible work arrangements. However, these employees tend to switch jobs quickly if their expectations or personal values are not met, raising concerns about their organizational commitment. It is therefore important to examine Generation Z’s commitment through the lens of person-job fit, as it encompasses the values they uphold. This study aims to investigate the relationship between person-job fit and organizational commitment, with job satisfaction as a mediating variable. A survey was administered to 236 Generation Z employees, and the data were analyzed using path analysis. The results showed that job satisfaction partially mediates the relationship between person-job fit and organizational commitment. Moreover, person-job fit has a direct effect on organizational commitment, both with and without the mediating role of job satisfaction. These findings highlight the importance of aligning Generation Z employees’ values with organizational values.